Sustainability through Lean Healthcare and Operational Performance in the Private Hospitals: A Proposed Framework - Azyyati Anuar; Rohaizah Saad; Rushami Zein Yusoff (International Journal of Supply Chain Management, 2018)
The Strategy Canvas that has been reported in the Eleventh Malaysia Plan, has targeted the government to improve community healthcare and yet to deliver a better service health outcomes with the strengthening collaboration among private sectors and Non-Governmental Organization (NGOs). To have a better health outcomes, lean management will be implemented to reach efficiency and optimize resources by improving work processes in the organization. But how far the private hospitals enable to survive in the long period where it can be seen the statistic of number of private hospitals is fluctuate. It indicates there are some possible factors could happen that affect the operations of the private hospitals and yet the profitability highly vulnerable. Certainly, one of the main reasons for the private hospitals is how they tolerate unnecessary waste in the organization. As such, the researcher will look deeply into how lean healthcare practices and operational performance will lead to sustainability in the private hospital by taking into account the triple bottom line; namely the financial, social, and environmental elements. Furthermore, a conceptual framework will be presented in this paper.